2019
DOI: 10.1186/s13063-019-3885-3
|View full text |Cite
|
Sign up to set email alerts
|

A disorder-specific group cognitive behavior therapy for social anxiety disorder in adolescents: study protocol for a randomized controlled study

Abstract: BackgroundSocial anxiety disorder (SAD) is a common disorder in adolescence associated with extensive distress and long-term impairment. Generic cognitive behavior therapy (CBT) programs for anxiety disorders have shown poorer outcomes for adolescents with SAD than for other anxiety disorders.AimThe aim of the present study is to investigate the efficacy of a disorder-specific group cognitive behavior therapy (G-CBT) program for youth SAD, the Cool Kids Anxiety Program - Social Enhanced (CK-E), developed at Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Social anxiety is the third biggest mental problem after drug use and depression, it is estimated that the prevalence in the general population is around 3% -13% in various countries. (Yuniardi, 2019) Early adolescents (13-18 years) experience many social anxiety disorders, where the number of female sufferers is higher than male adolescents (Lassen et al, 2019;(Jefferies & Ungar, 2020). The high number of adolescents who experience social anxiety requires immediate treatment so that adolescent social anxiety does not continue which can cause negative effects on their future lives such as the risk of developing chronic depression in adulthood, suicidal ideation, alcohol use, drug abuse, and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Social anxiety is the third biggest mental problem after drug use and depression, it is estimated that the prevalence in the general population is around 3% -13% in various countries. (Yuniardi, 2019) Early adolescents (13-18 years) experience many social anxiety disorders, where the number of female sufferers is higher than male adolescents (Lassen et al, 2019;(Jefferies & Ungar, 2020). The high number of adolescents who experience social anxiety requires immediate treatment so that adolescent social anxiety does not continue which can cause negative effects on their future lives such as the risk of developing chronic depression in adulthood, suicidal ideation, alcohol use, drug abuse, and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta‐analysis demonstrated that youth with SAD were almost 50% less likely to remit from their primary diagnosis after this type of treatment compared to those with other anxiety disorders (Evans, Clark, & Leigh, 2021 ). These findings have led to renewed efforts to develop SAD‐specific interventions (Lassen, Hougaard, Arendt, & Thastum, 2019 ). In this context, the notably large effect sizes associated with certain treatments for adult SAD are of interest.…”
Section: Introductionmentioning
confidence: 99%